Fluorescence Spectroscopy and Silica Gel Applied as a Tool for Capture and Detection of Compressor Lubricant Oils - Yamamoto Morassuti, Claudio; Lima, Sandro Marcio; da Cunha Andrade, Luis Humberto (Orbital: The Electronic Journal of Chemistry, 2023)
Here, we report the use of fluorescence spectroscopy for the identification of lubricant oils used in reciprocating compressors, and the use of silica gel as an adsorbent to capture lubricant oil vapors. The silica gel was tested for adsorption of lubricant oil vapors, by heating the samples at 200°C, the emission spectrum of the lubricant oils is observed on the silica gel layer, over 20 min of heating. The spectrum of the lubricant oils over the silica gel layer presents a redshift, an indication of the degradation effect. In order to investigate this effect on the optical properties, we conducted an experiment by heating the samples at (130 ± 4) °C, and collected at different times. The MID-infrared absorption of the samples presents bands of oxygen-containing groups at 1010 and 1050 cm-1, and NIR infrared absorption measurements at 3444 cm-1 show an increase in the hydroperoxide band during the degradation time. These two results indicate that the oxidation process is associated with the observed redshift of the absorption and emission bands in lubricant oils and over the adsorbent layer.